Dynamic decision processes in complex, high-risk operations: The Yarnell Hill Fire, June 30, 2013. (January 2015) - Hardy, Karim; Comfort, Louise K.
Highlights: Wildland firefighting within high-risk and uncertain environment leads to inadequate competencies. Lack of communication is a main concern in large and intensive fires due to increasing of complexity. Dynamic flows of information are challenging to make adequate decisions in unstable situations. Abstract: Recreating the information flow in decision processes after serious accidents enables researchers and policy makers to identify both the threshold points at which action begins to fail and gaps in information processes that could be corrected to reduce risk in future incidents. The Yarnell Hill Fire of 30 June 2013 occurred in a rapidly changing, high-risk environment of the Arizona highlands in which the interaction among the physical terrain, wind and vegetation conditions, technical support structures, and organizational decision processes led to the collapse of the firefighting strategy and the loss of nineteen members of the Granite Mountain Interagency Hotshot Crew. Based on documentation from operational management manuals, accident reports, and agency records, simulation methods are used to retrace the information flow in this complex decision process and reveal fresh insights into the limitations of standard firefighting practices in rapidly escalating, dangerous, wildfire conditions.